Pro-inflammatory fatty acid profile and colorectal cancer risk: A Mendelian randomisation analysis. (October 2017) - May-Wilson, Sebastian; Sud, Amit; Law, Philip J.; Palin, Kimmo; Tuupanen, Sari; Gylfe, Alexandra; Hänninen, Ulrika A.; Cajuso, Tatiana; Tanskanen, Tomas; Kondelin, Johanna; Kaasinen, Eevi; Sarin, Antti-Pekka; et al.
Abstract: Background: While dietary fat has been established as a risk factor for colorectal cancer (CRC), associations between fatty acids (FAs) and CRC have been inconsistent. Using Mendelian randomisation (MR), we sought to evaluate associations between polyunsaturated (PUFA), monounsaturated (MUFA) and saturated FAs (SFAs) and CRC risk. Methods: We analysed genotype data on 9254 CRC cases and 18, 386 controls of European ancestry. Externally weighted polygenic risk scores were generated and used to evaluate associations with CRC per one standard deviation increase in genetically defined plasma FA levels. Results: Risk reduction was observed for oleic and palmitoleic MUFAs (OROA = 0.77, 95% CI: 0.65–0.92, P = 3.9 × 10 −3 ; ORPOA = 0.36, 95% CI: 0.15–0.84, P = 0.018). PUFAs linoleic and arachidonic acid had negative and positive associations with CRC respectively (ORLA = 0.95, 95% CI: 0.93–0.98, P = 3.7 × 10 −4 ; ORAA = 1.05, 95% CI: 1.02–1.07, P = 1.7 × 10 −4 ). The SFA stearic acid was associated with increased CRC risk (ORSA = 1.17, 95% CI: 1.01–1.35, P = 0.041). Conclusion: Results from our analysis are broadly consistent with a pro-inflammatory FA profile having a detrimental effect in terms of CRC risk.